Land Tenure in Slum Upgrading Projects - (:unkn) unknown (My University, 2011)
This paper gives an overview of slum upgrading in Kenya observing that slums are a major urban housing phenomena in Kenya that require immediate attention. Rather than demolishing them, which renders many people homeless, they should be upgraded through tenure security and infrastructure improvement so as to provide a better living environment for the residents currently living in the settlements.
Keywords: African Research